ИССЛЕДОВАНИЕ ОНТОГЕНИЧЕСКИХ И СТЕРЕОМЕТРИЧЕСКИХ ОСОБЕННОСТЕЙ СТРОЕНИЯ И НЕКОТОРЫХ ТЕХНОЛОГИЧЕСКИХ СВОЙСТВ РУДНЫХ АГРЕГАТОВ (НА ПРИМЕРЕ РУД АЛЕКСАНДРИЙСКОГО МЕСТОРОЖДЕНИЯ, УРАЛ) - Бродская Р.Л.; Бильская И.В.; Кобзева Ю.В.; Ляхницкая В.Дм. (My University, 2005)
One of the technological mineralogy problems - the complete and energysaving disintegration - was analyzed from the viewpoint of structural organization of a mineral aggregate, i. e. character and energy of intergrowths along boundaries of mineral individuals in it. It is shown that energy-consuming and energy-satiated boundaries of mineral grains, absorbing, while their formation and destruction, different amounts of energy, are formed at different stages of the aggregate development and, thus, they arc connecting with its genesis and ontogenesis. The roughness of energy-consuming and hardly-disclosured boundaries of intergrowths and individuals correlates with their crystallographic peculiarities and their specific superficial energy. To realize the forecasting of an ore aggregate quality in its geometrical and energetic selectivity for disintegration, and to use it in technological processing scheme, it is necessary to input the measure and share of geometrical and topological roughness of surface and a cross-section contour of mineral grains, taking into consideration matrix of mineral intergrowths and the matrix of intergrowths between individuals of one mineral but related to different its generations. There arc considered methodical possibilities to use apparatus of Fourier analysis and the fractal dimension evaluation, and displayed the methodical study data on natural types of ores of Aleksandrinsky massive sulfide poly-metallic ore deposit (the Urals).